2020
DOI: 10.3390/cancers12082038
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Host, Lifestyle and Environmental Factors in the Pathogenesis of MPN

Abstract: Philadelphia-negative myeloproliferative neoplasms (MPNs) occur when there is over-production of myeloid cells stemming from hematopoietic stem cells with constitutive activation of JAK/STAT signaling, with JAK2V617F being the most commonly occurring somatic driver mutation. Chronic inflammation is a hallmark feature of MPNs and it is now evident that inflammation is not only a symptom of MPN but can also provoke development and precipitate progression of disease. Herein we have considered major MPN driver mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 96 publications
1
9
0
Order By: Relevance
“…Polynesians smoke more tobacco and have higher rates of obesity, which increases the risk of certain cancers [ 31 , 32 , 33 ], and is of relevance in MPN [ 34 , 35 , 36 , 37 , 38 , 39 ]. Risk factors for MPN remain poorly defined; however, certain modifiable lifestyle factors have been implicated (e.g., diet, smoking, alcohol and coffee consumption, psychological stress and physical activity), as well as certain chemical exposures (e.g., benzene and polycyclic aromatic hydrocarbons) [ 39 , 40 ]. Better definition of the roles of these risk factors in MPN pathogenesis may help design new preventative strategies against MPN.…”
Section: Discussionmentioning
confidence: 99%
“…Polynesians smoke more tobacco and have higher rates of obesity, which increases the risk of certain cancers [ 31 , 32 , 33 ], and is of relevance in MPN [ 34 , 35 , 36 , 37 , 38 , 39 ]. Risk factors for MPN remain poorly defined; however, certain modifiable lifestyle factors have been implicated (e.g., diet, smoking, alcohol and coffee consumption, psychological stress and physical activity), as well as certain chemical exposures (e.g., benzene and polycyclic aromatic hydrocarbons) [ 39 , 40 ]. Better definition of the roles of these risk factors in MPN pathogenesis may help design new preventative strategies against MPN.…”
Section: Discussionmentioning
confidence: 99%
“…Atherosclerosis is a chronic inflammatory disease, which involves several circulating blood cells, including both leukocytes and platelets 58–62 . Taking into account that chronic inflammation today is considered of utmost importance in MPN‐pathogenesis 3,8–33 and MPNs carry an increased risk of chronic inflammatory diseases, such as inflammatory bowel diseases, age related macular degeneration, and chronic kidney diseases, which all are associated with early development of atherosclerosis, 3,6,8,10 we speculated if whole blood gene expression profiling of all the inflammatory cells (e.g., granulocytes, monocytes, platelets) being involved in the atherosclerotic process might unravel deregulation of atherosclerosis genes and perhaps depict a particular MPN‐atherosclerosis gene signature. Indeed, in the present study, we found a higher percentage of deregulated genes among the 84 atherosclerosis genes in patients with ET, PV, or PMF compared to deregulated genes among the full list of genes for the three patient groups.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, both apoptosis and proliferation are involved in the pathophysiology of atherosclerosis and its progression (see below). As noted above atherosclerosis is prevailing in several chronic inflammatory diseases, such as type 2 diabetes mellitus (T2DM) but also in MPNs, in which accelerated atherosclerosis with increased aortic and valvular calcifications 54 and an increased risk of aneurysms 52,64,65 may be attributed to the enhanced inflammatory 8–29,66 and oxidative stress load in patients with MPNs 31,32,55,67–69 . Although the JAK2V617F mutation has been convincingly demonstrated to associate with generation of ROS, 31 even in the very early phase of MPN‐development—the CHIP‐ JAK2V617F stage—in which oxidative stress may elicit the malignant JAK2V617F clone and contribute to its expansion toward overt MPN, 70 it is intriguing to note that a most recent study has shown that the CALR mutation more strongly than the JAK2V617F mutation increases both oxidative stress and DNA damage‐related genomic instability in patients with myelofibrosis 71 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clonal populations of dysplastic megakaryocytes and myeloid cells release inflammatory cytokines that are responsible for clonal evolution, symptom burden, progressive myelofibrosis and extramedullary splenic hematopoiesis 12 . Risk factors for acquired PMF include smoking, excessive alcohol intake, exposure to radiation, or exposure to industrial solvents 13 . Common gene mutations found in patients with PMF include Janus kinase 2 (JAK2V617F), calreticulin (CALR), thrombopoietin receptor (MPL515L/K), and ten-eleven translocation 2 (TET2).…”
Section: Introductionmentioning
confidence: 99%